Art and social construction of the landscape in Peralta, Turrialba - Sibaja Solís, A. Mario (2023)
Landscapes are socially constructed in everyday life from the present, based on values and meanings that in the past had make it, thus inheritance, it implies an aspiration to remember in the future the spacial shape which have given its figure and meaning. Despite the political and economic processes that have promoted the invisibility of certain particular landscapes, art can be outlined as a strategy for the dissemination and visibility of cultural codes that were systematically forgotten. Hence, Peralta in Turrialba, is presented as an open-air gallery, where the community redeems through art, past landscapes which make sense in the present, and will be objects of desire and dreams in the future. The article discusses the artistic expressions surrounding the central park of Peralta, showing shared values in the landscape building. Imaginaries and presence/absence, crystallized regarding art and landscape.